APPLICATION OF ARTIFICIAL NEURAL NETWORK BACKPROPAGATION FOR PREDICTING THE AVAILIBILITY OF PREMIUM FUEL (CASE STUDY: PREDICTION OF PREMIUM FUEL AVAILIBILITY ON SPBU GALALA AMBON) - Vicky Riyadi; E. R. Persulessy; Y. A. Lesnussa (Pattimura Proceeding, 2017)
This study aims to predicting the availability of premium fuel using pattern recognition techniques named neural network with backpropagation method. Neural network is used to give solution for many problem, including taking a decision from the training data. Neural network can be applied to various specific fields of human life. In this study, Neural Network is used to predict the availability of premium fuel using backpropagation method. The data which is used in this study consist of 48 data, where 36 data (years 2012-2014) as training and 12 data (years 2015-2016) as testing. The result shows that the availability of premium fuel in 2017 for 12 months with the prediction results availability in January 2017 is 337490 kL and December 2017 is 344120 kL. It can be seen that the prediction results to be achieved fully met with a small error rate and the level of accuracy 83.33% where the results of the testing data showed the value of Mean Square Error for prediction the availability of premium fuel in 2017 is and also to the process of training produces the best network architecture with hidden layer 20 10 5 1 neurons and the best training algorithm by using learning rate 0.74 with MSE 0.00100. Thus, Backpropagation method is pretty well in predicting the availability of fuel.